Serum levels of bone formation and resorption markers in relation to vitamin D status in professional athletes and physically active men during upper and lower body high-intensity exercise - Waldzinski, T.; Waldzinska, E.; Mieszkowski, J.; Niespodzinski, B.; Stankieiwcz, B.; Durzynska, A.; Brzezinska, P.; Kochanowicz, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Several reports on the effect of single exercise and regular training on bone marker levels have been published; however, the data are not consistent. Without a doubt, exercise intensity and its nature, in conjunction with dietary factors, determine the bone marker response. Of note, many indoor athletes who practice certain sports are vitamin D-deficient. Vitamin D plays an important role in bone metabolism. It also influences skeletal muscle strength, reduces muscle atrophy and parathyroid hormone concentration, and exerts many other effects . Despite of these positive effects, to the best of our knowledge, the acute effect of exercise on bone formation and resorption markers in relation to vitamin D status had not yet been assessed. Hence, the primary aim of the current study was to evaluate the effects of vitamin D status on changes in the serum PINP and CTX levels induced by Wingate anaerobic test (WAnT) in highly trained athletes and untrained young men. METHODS: Sixteen elite male artistic gymnasts (EG; 21.4 ± 0.8 years-old) and 16 physically active men (the control group, PAM; 20.9 ± 1.2 years-old) performed lower and upper body 30-s Wingate anaerobic tests (LBWT and UBWT, respectively). For biomarker analysis, blood samples were collected before, and 5 and 30 min after exercise. Samples for vitamin D levels were collected before exercise. N-terminal propeptide of type I collagen (PINP) was analysed as a marker of bone formation. C-terminal telopeptide of type I collagen (CTX) was analysed as a marker of bone resorption. RESULTS: UBWT fitness readings were better in the EG group than in the PAM group, with no difference in LBWT readings between the groups. UBWT mean power was 8.8% higher in subjects with 25(OH)D3 levels over 22.50 ng/ml and in those with 24,25(OH)2D3 levels over 1.27 ng/ml. Serum CTX levels increased after both tests in the PAM group, with no change in the EG group. PINP levels did not change in either group; however, in PAM subjects with 25(OH)D3 levels above the median, they were higher than those in EG subjects CONCLUSION: Vitamin D metabolites affect the anaerobic performance and bone turnover markers at rest and after exercise. Further, adaptation to physical activity modulates the effect of anaerobic exercise on bone metabolism markers.